Progressive reduction in skeletal muscle mass to visceral fat area ratio is associated with a worsening of the hepatic conditions of non-alcoholic fatty liver disease - Shida T (Dove Medical Press, 2019)
Takashi Shida,1 Natsumi Oshida,2 Sechang Oh,3 Kosuke Okada,1 Junichi Shoda41Tsukuba Preventive Medicine, Research Center, Tsukuba University Hospital, Tsukuba, Ibaraki, Japan; 2Master Programs in Medical Sciences, Graduate School of Comprehensive Human Sciences, University of Tsukuba, Tsukuba, Ibaraki, Japan; 3The Center for Sports Medicine and Health Sciences, Tsukuba University Hospital, Tsukuba, Ibaraki, Japan; 4Medical Sciences, Faculty of Medicine, University of Tsukuba, Tsukuba, Ibaraki, JapanBackground: Deceased muscle mass combined with increased visceral fat mass is reportedly linked to a higher risk of worsening the hepatic conditions of non-alcoholic fatty liver disease (NAFLD).Objective: The aim of this study was conducted in a retrospective manner to investigate whether longitudinal changes in skeletal muscle mass to visceral fat area ratio (SV ratio), an index of sarcopenic obesity, are influential on the hepatic conditions and pathophysiology of NAFLD during the clinical course.Design: The association of SV ratio with hepatic conditions and pathophysiology was evaluated longitudinally for 2–5.5 years (median 4.1 years) in 92 patients with NAFLD (36 men and 56 women; 17–78 years). The subjects were divided into three groups according to the change in their SV ratio: improved, stable, or worsened, and the changes in parameters associated with NAFLD were compared among the groups.Results: In the group with a worsened SV ratio, visceral fat area increased (122±30–138±30 cm2,; mean ± SD), whereas total muscle mass decreased (26.5±6.1–25.9±5.9 kg), which was especially noticeable in the lower extremities (14.8±3.3–14.3±3.1 kg). In accordance with the change of body composition, transient elastography showed higher levels of liver stiffness (7.7±5.4–9.0±6.0 kPa) and fat accumulation (265±43–293±48 dB/m). There were also higher levels of fasting plasma glucose (115±29–126±40 mg/dL) and HbA1c (6.0±1.1–6.3±1.0%). In contrast, deterioration in these parameters did not occur in the groups with improved or stable SV ratios.Conclusion: Collectively, a progressive reduction in skeletal muscle mass accompanied by an increase in visceral fat mass during the clinical course of NAFLD is associated with a worsening of the hepatic conditions, fat accumulation and progression of fibrosis.Keywords: non-alcoholic fatty liver disease, skeletal muscle mass to visceral fat area ratio, sarcopenic obesity, hepatic steatosis, hepatic fibrosis, clinical course